2021
DOI: 10.3390/ani11071863
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Functional Analysis of CircRNA in the Ovaries of Low and High Fecundity Hanper Sheep

Abstract: Litter size is a considerable quality that determines the production efficiency of mutton sheep. Therefore, revealing the molecular regulation of high and low fertility may aid the breeding process to develop new varieties of mutton sheep. CircRNAs are the important factors regulating follicular development, but their mechanism role in the regulation of litter size in Hanper sheep is not clear. In the present study, ovarian tissues from the follicular (F) or luteal phase (L) of Hanper sheep that were either co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
(61 reference statements)
4
12
0
Order By: Relevance
“…These circular RNAs are mainly composed of three types (Fig 1D ), introns (8%3%), intergenic (3.4%8.4%) and exons (both 88.6%). The sequencing results in the ovaries of previous studies, such as pig (Wang et al, 2021), goat (La et al, 2019) and sheep (Liu et al, 2021) animals, were similar to the results obtained in the present study.…”
Section: Identification Features and Characteristics Of Circrnassupporting
confidence: 91%
“…These circular RNAs are mainly composed of three types (Fig 1D ), introns (8%3%), intergenic (3.4%8.4%) and exons (both 88.6%). The sequencing results in the ovaries of previous studies, such as pig (Wang et al, 2021), goat (La et al, 2019) and sheep (Liu et al, 2021) animals, were similar to the results obtained in the present study.…”
Section: Identification Features and Characteristics Of Circrnassupporting
confidence: 91%
“…miR-27a inhibits the proliferation and promotes the apoptosis of mouse granulosa cells by reducing key enzymes for estrogen synthesis [87]. The sequencing of follicular and luteal phase ovarian tissues from monotocous and polytocous sheep revealed that oar-miR-181a (target to novel_circ_0017815) and oar-miR-27a have a targeting relationship with circLTBP1 [88]. miR-181a was also found to be associated with the regulation of estradiol synthesis and follicular apoptosis [89,90].…”
Section: Regulatory Network Of Mirnas and Circrnasmentioning
confidence: 99%
“…CircRNAs are known to promote the transcription of source genes by interacting with U1 small ribonucleoproteins (snRNPs) and RNA polymerase II ( 41 ). Therefore, identification of the potential functions of source genes associated with circRNAs may shed light out on their functions ( 42 ). In this study, the source genes of differentially expressed circRNAs found to been riched in Inositol phosphate metabolism, cGMP-PKG signaling pathway, Calcium signaling pathway, MAPK signaling pathway and Oocyte meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Oar-miR-377-3p is related to oocyte quality, this can directly affect the ability of the embryo to develop ( 64 ). Oar-miR-181a, oar-miR-432 and oar-miR-495-3p were identified to be associated with reproductive function ( 42 , 65 ). Oar-miR-21, oar-miR-370-3p, and oar-miR-10b are differentially expressed in sheep-related diseases ( 66 , 67 ), which have not been studied in seasonal reproduction, their differential expression under different photoperiods deserves further study.…”
Section: Discussionmentioning
confidence: 99%